2020
DOI: 10.1155/2020/3717506
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Leiomyoma with Synchronous Solitary Fibrous Tumor of the Pleura

Abstract: Bladder leiomyomas (BLs) are extremely rare benign tumors of mesenchymal origin. The exact pathophysiological mechanisms that lead to their appearance remain unclear including hormonal disorders, chromosomal abnormalities, and fetal remnants in the bladder. They usually remain asymptomatic for a long period of time. Solitary fibrous tumors (SFTs) are also rare neoplasms of mesenchymal origin with malignant potential usually affecting the pleura. The pathogenesis of SFTs remains unclear. We report the case of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…As recent studies have shown promise in establishing best practices for evaluation and management, we reviewed the related studies on the last five years between 2016 and 2021. To review the features of bladder leiomyoma such as symptoms, diagnosis tools, treatment and prognosis, a literature search of PubMed and the Web of Science was conducted, which included 22 cases of bladder leiomyomas in 17 publications as shown in Table 1 (1,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The symptoms vary according to the location of the tumor, and may even be asymptomatic (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…As recent studies have shown promise in establishing best practices for evaluation and management, we reviewed the related studies on the last five years between 2016 and 2021. To review the features of bladder leiomyoma such as symptoms, diagnosis tools, treatment and prognosis, a literature search of PubMed and the Web of Science was conducted, which included 22 cases of bladder leiomyomas in 17 publications as shown in Table 1 (1,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The symptoms vary according to the location of the tumor, and may even be asymptomatic (Table 1).…”
Section: Discussionmentioning
confidence: 99%